Uses of digital social networks for collective action: the case of «Ni Una Menos» - Caballero, Gerardo (2019)
The following article seeks to show the role that digital social networks play in the episodes of mobilization and collective action, through a case study: the march against violence against women that took place on August 13, 2016 in Lima and other cities of the country, under the slogan «Ni Una Menos».The study describes the ways in which the different tools and services of Facebook (status update, messenger, groups, fanpage) facilitate a series of indispensable processes for collective action: emergence of outrage, emotional activation, deliberation, coordination, organization and dissemination of information.It also shows that in the event that internal tensions arise in the process of mobilization, these are also reproduced in the spaces provided by digital social networks.